2008
DOI: 10.1016/j.jtcvs.2007.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial revascularization to enhance myocardial vasculogenesis and hemodynamic function

Abstract: Transmyocardial laser revascularization with the holmium-YAG laser enhances perfusion, with resultant improvement in myocardial contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 41 publications
0
28
1
1
Order By: Relevance
“…96 In our study, we found that TMR's beneficial effect on LV function is due to increased engraftment of circulating MSCs (discussed below). Therefore, we hypothesize that part of the clinical therapeutic benefit of TMR might be attributable to TMR-induced transmigration and engraftment of circulating progenitor cells, although the source and number of these cells are yet to be clearly delineated.…”
Section: Tmr Increases Donor Msc Engraftmentmentioning
confidence: 60%
See 3 more Smart Citations
“…96 In our study, we found that TMR's beneficial effect on LV function is due to increased engraftment of circulating MSCs (discussed below). Therefore, we hypothesize that part of the clinical therapeutic benefit of TMR might be attributable to TMR-induced transmigration and engraftment of circulating progenitor cells, although the source and number of these cells are yet to be clearly delineated.…”
Section: Tmr Increases Donor Msc Engraftmentmentioning
confidence: 60%
“…This finding is at odds with the evidence presented by Woo and colleagues and Cooley et al of increased vascular densities. 93,96 The trends observed in the capillary densities suggested that the groups that underwent TMR had greater angiogenesis, compared to the ones that did not receive TMR. This is consistent with our previous data, as we saw greater vascular densities in the groups treated with TMR.…”
Section: Effect Of Tmr On Vascular Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In reality, the channels are occluded shortly after creation, but interestingly there is maintenance of enhanced perfusion by neovasculature with clinical resolution of angina. 1, 2 Since 1997, with publication of the seminal work defining endothelial progenitor cells (EPCs) by Dr Asahara and colleagues there have been many studies attempting to enhance myocardial perfusion using various EPC mediated strategies. 3 A dichotomy has developed on the approach to enhancing angiogenesis between exogenous administration of EPCs and utilizing the potent EPC chemokines, ie, stromal cell-derived factor (SDF)-1α, vascular endothelial growth factor (VEGF), hepatocyte growth factor, basic fibroblast growth factor (BFGF), and placental growth factor (PlGF), to upregulate and potentiate the preexisting endogenous reparative process.…”
Section: Article P 916mentioning
confidence: 99%